A new One Health Framework in Qatar for future emerging and re-emerging zoonotic diseases preparedness and response - Devendra, Bansal (2023)
One Health is increasingly recognized as an optimal approach to address the global risk of health threats originating at the human, animal, and ecosystem interface, and their impact. Qatar has successfully practiced One Health approach for investigation and surveillance of zoonotic diseases such as MERS-CoV, and other health threats. However, the current gaps at institution and policy level hinder the sustainment of One Health. In this paper, we have assessed the potential for implementation of One Health Framework to reinforce and sustain One Health capacities in Qatar for 2022–2027. To implement One Health Framework in the country, Qatar Joint External Evaluation (JEE) report, lessons learnt during One Health experiences on zoonotic, vector-borne, and food borne diseases were used to present an outline for multisectoral coordination. In addition, technical capacities of One Health and factors that are required to operationalize it in the country were also assessed in series of meetings and workshops held at Ministry of Public Health on March 2022. Present health care infrastructure and resources were found to be conducive for effective management and response to shared health threats as evident during MERS-CoV, despite being more event based. Regardless, the need for more sustainable capacity development was unanimously emphasized. The consensus between all relevant stakeholders and partners was that there is a need for better communication channels, policies and protocols for data sharing, and the need to invest more resources for better sustainability. The proposed framework is expected to strengthen and facilitate multilateral coordination, enhanced laboratory capacity and network, improve active surveillance and response, risk communication, community engagement, maximize applied research, and build One Health technical work force. This would enable advancement and sustainment of One Health activities to prevent and control health threats shared between humans-animals-ecosystem interface.